2022
DOI: 10.1098/rsob.220111
|View full text |Cite
|
Sign up to set email alerts
|

The immune deficiency and c-Jun N-terminal kinase pathways drive the functional integration of the immune and circulatory systems of mosquitoes

Abstract: The immune and circulatory systems of animals are functionally integrated. In mammals, the spleen and lymph nodes filter and destroy microbes circulating in the blood and lymph, respectively. In insects, immune cells that surround the heart valves (ostia), called periostial haemocytes, destroy pathogens in the areas of the body that experience the swiftest haemolymph (blood) flow. An infection recruits additional periostial haemocytes, amplifying heart-associated immune responses. Although the structural mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 119 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…While demonstration of dsRNA uptake by mosquito hemocytes suggests they may also play such a role, evidence of downstream RNAi activity is lacking (Airs et al, 2023). A number of sequencing experiments have also identified interconnectivity between the molecular innate immune pathways (IMD, Toll, JAK-STAT) and hemocyte activity during Plasmodium and bacterial infection of Anopheles spp, but this has not been replicated in a mosquito-virus system (Ramirez et al, 2014;Yan et al, 2022).…”
Section: The Role Of Mosquito Hemocytes During Viral Infection Remain...mentioning
confidence: 99%
“…While demonstration of dsRNA uptake by mosquito hemocytes suggests they may also play such a role, evidence of downstream RNAi activity is lacking (Airs et al, 2023). A number of sequencing experiments have also identified interconnectivity between the molecular innate immune pathways (IMD, Toll, JAK-STAT) and hemocyte activity during Plasmodium and bacterial infection of Anopheles spp, but this has not been replicated in a mosquito-virus system (Ramirez et al, 2014;Yan et al, 2022).…”
Section: The Role Of Mosquito Hemocytes During Viral Infection Remain...mentioning
confidence: 99%
“…Details of mosquito phagocytic interactions with parasites and pathogens are given in other papers in this Special Issue and have been published previously [ 15 , 102 , 118 , 120 , 121 , 122 , 123 , 124 , 125 ]. Granulocytes are the main phagocytes in mosquitoes and comprise about 90% of the haemogram of which there are ca.…”
Section: Vector Cellular Immunitymentioning
confidence: 99%
“…A fascinating study on the mosquito responses to Plasmodium has shown that infection results in recruitment of additional periosteal haemocytes to amplify the heart-related immune response. This results from the upregulation of the IMD and JNK signaling pathways (see Section 6 on recognition, below) which enhances this periosteal haemocyte aggregation, activating phagocytosis and melanisation in the heart, thereby demonstrating the integration of the response between the immune and circulatory systems [ 125 ]. The freely circulating haemocytes were not affected in a similar way.…”
Section: Vector Cellular Immunitymentioning
confidence: 99%